CARICOM states and the Group of Three : a new partnership between Latin America and the non-Hispanic Caribbean? - Serbin, Andres (1991)
Notes that Caribbean states recognise that regardless of economic imbalances and/or cultural and political differences, the non-Hispanic Caribbean and Latin America have more in common with one another than with any other part of the world - Latin America's.